Susceptibility of Simulium damnosum complex larvae to temephos in the Tukuyu onchocerciasis focus, southwest Tanzania - Kalinga, A K; Mweya, C N; Barro, T; Maegga, B T (Tanzania Journal of Health Research, 2007)
Tukuyu onchocerciasis focus was earmarked for vector control using insecticide against larval stages. Susceptibility tests of mature larvae of Simulium damnosum s.l. vectors to temephos insecticide were carried out before and after two years of insecticide treatment of rivers within Tukuyu onchocerciasis focus, south-western Tanzania. The tests were done in 1999/2000 and 2004 using WHO standard methods. Mature larvae were exposed to 9 concentrations of temephos active ingredient, from the weakest 0.00975mg/litre to the strongest of 2.5mg/l. Each test concentration and control was run in duplicates of 25 larvae each, set for three hours in a cool temperature. After incubation, test solution was discarded and larval condition checked. Numbers of larvae in each category were recorded and used to determine mortality rate for each concentration as well as for the LC50 and LC95. A total of 1,666 larvae were tested, 942 during the pre- and 724 post-treatment. Results showed that both pre and post-treatment samples were susceptible, attaining 100% mortality at the diagnostic dose of 1.25mg/l, and LC50 between 0.129-0.34mg/l pre - and 0.144-0.211 mg/l (95% CI, P<0.05) post- treatment. These values fall within the standard diagnostic dose of ≤0.4mg/l for susceptible S. damnosum s.l populations. It was concluded that the endemic S. damnosum population was susceptible to temephos before and after two years of intermittent field application. Temephos was thus recommended for continued use in onchocerciasis vector control in the Tukuyu focus, to complement Community Directed Treatment with Ivermectin, but close monitoring of vector susceptibility should be done. Keywords: susceptibility, Simulium damnosum, control, temephos, Tanzania Tanzania Health Research Bulletin Vol. 9 (1) 2007: pp. 19-24